The Grapes of Wrath movie still. - 20th Century Fox:::Creator::::::::::::
The Grapes of Wrath movie still. Tom Joad (Henry Fonda) and JIm Casy (John Carradine). RESTRICTED USE Digital copy only. No hard copy.